1987
DOI: 10.1080/00380768.1987.10557599
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Hydroxy-Sodalite (“Zeolite”) from Waste Coal Ash

Abstract: A large amount of waste ash is produced by the plants such as thermal power stations which are using coal and/or pulverized coal for fuel. There are about 40 large thermal power stations in Japan, and they are discharging approximately 2 million ton

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
44
0
23

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(67 citation statements)
references
References 2 publications
0
44
0
23
Order By: Relevance
“…These results suggest that hybrid zeolite/glass samples were densified by infiltration of the liquid phase of glass over 700°C (liquid sintering process). Furthermore, for these hybrid zeolite/glass samples with glass contents, the increase of glass content subsequently led to the high density because soda-lime glass has the higher density of 2.4 g/cm 3 , compared to A-zeolite.…”
Section: Kamitani Et Al: Fabrication and Evaluation Of Hybrid Materimentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that hybrid zeolite/glass samples were densified by infiltration of the liquid phase of glass over 700°C (liquid sintering process). Furthermore, for these hybrid zeolite/glass samples with glass contents, the increase of glass content subsequently led to the high density because soda-lime glass has the higher density of 2.4 g/cm 3 , compared to A-zeolite.…”
Section: Kamitani Et Al: Fabrication and Evaluation Of Hybrid Materimentioning
confidence: 99%
“…Figure 8 shows the variation of density with calcinations temperatures and glass contents for hybrid zeolite/glass samples heat-treated at 600 to 800°C for 2 h. Samples heated at 600°C had the almost same density as well as compaction before calcinations. The typical density of A-zeolite and soda-lime glass is 1.6 and 2.4 g/cm 3 , respectively. Samples heated at 700°C had the higher density than ones heated at 600°C.…”
Section: Kamitani Et Al: Fabrication and Evaluation Of Hybrid Materimentioning
confidence: 99%
“…Some studies indicated that zeolite can be synthesized from coal fly ash [3,4] or paper sludge ash [5]. Other studies also indicated synthesis of zeolites from diatomite [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…An Na-P1 type artificial zeolite (Na 6 Al 6 Si 10 O 32 ·12H 2 O) having a high cation exchange capacity (CEC) is able to be synthesized at a low cost using alkali from the waste coal fly ash of thermal power stations. 6)9) The Na-P1 type artificial zeolite has a high Cs + ion adsorption ability and high CEC value. In our previous paper, we evaluated the conditions for the Na-P1 type zeolite preparation and synthesized the composite material (magnetic zeolite) of the Na-P1 type zeolite and nanosized magnetite by alkali processing from a mixed solution of the fly-ash and iron chlorides for the magnetic collection of the zeolite after the Cs + ion adsorption.…”
Section: Introductionmentioning
confidence: 99%